Aktivitas Komunikasi Pemasaran Digital Pada Toko Antik Keris Melalui Marketplace Shopee Untuk Meningkatkan Penjualan - Nagara, Michael Isra; Hastuti, Nurnawati Hindra; Widiyowati, Estu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
In modern times like now, people have started to switch to using digital media to carry out their daily activities, including in the field of marketing. Antik Keris Shop is one of the many businesses that choose to market their products online. Antik Keris Shop chose the Shopee marketplace as a means to market its products. Digital marketing communication activities can be used to achieve an increase in sales. By using marketing communication activities, the Antik Keris shop is able to influence consumers' interest in choosing the products offered. The aim of this research is to determine and analyze the digital marketing communication activities of the Antik Keris shop on the Shopee marketplace to increase sales. This research uses the concept of Digital Marketing Communication by Philip Kotler and Gary Armstrong. The research method used by researchers in this research is a qualitative method with a descriptive approach. Data collection techniques were carried out by researchers through interviews and documentation. The results of this research show that the Antik Keris shop uses digital marketing communication activities to increase sales. The digital marketing communication activities used include advertising and sales promotions. The two digital marketing communication activities used will complement each other to achieve an increase in sales. Keywords : Digital Marketing Communication, Shopee Marketplace, Increased sales